1963
DOI: 10.1530/jrf.0.0060099
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Recovery of Fertility in Mice After Protracted Steroid-Induced Sterility

Abstract: Females of strain BALB were maintained sterile for 13 to 20 months by the subcutaneous implantation of pellets containing 40% of 19-nor-progesterone. The life-span of the treated animals was not shorter than that of normal breeding females. Pregnancy can still take place when the pellet is removed after having caused sterility during 395 days, i.e. till the moment when, in normal animals, 98 % of the reproductive task has been fulfilled.The females emerging from a steroid-induced sterility of 395 days behaved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1968
1968
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The finding that more animals are born in the second or in succeeding litters than in the first litter is present in data by Ingram et al (1958), King (1916), Asdell', Bogart, and Sperling (1941), Biggers. Finn, andMcLaren (1962), andLipschultz, Iglesias, andSalinas (1963).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that more animals are born in the second or in succeeding litters than in the first litter is present in data by Ingram et al (1958), King (1916), Asdell', Bogart, and Sperling (1941), Biggers. Finn, andMcLaren (1962), andLipschultz, Iglesias, andSalinas (1963).…”
Section: Discussionmentioning
confidence: 99%
“…It does not appear to be related to the conservation of ova as a result of inhibition of ovulation during pregnancy. This possibility cannot be relevant to the fertility diflerences found between the first and the second pregnancies of young animals Shelton (1959) demonstrated that breeding does not significantly alter the rate of loss of oocytes, and Lipschultz et al (1963) showed that mice prevented from ovulation by implants of 19-nor-progesterone for two thirds of their reproductive life had the same degree of fertility when released from the implants as normally aging animals.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, Lauson, Golden & Sevringhaus (1939) (Hoogstra & Paesi, 1955;Ramirez & McCann, 1963;Barraclough, 1966;Moore, 1965Moore, /1966Matsuyama, Weisz & Lloyd, 1966 (Lipschutz, Igiesias & Salinas, 1963;Verzar, 1966). It appears that in the aged rat pituitary, fsh and lh levels are elevated at a time when ovaries are capable of responding to pmsg (Labhsetwar, 1967a) and the uterus retains the capacity to form deciduomata (Labhsetwar, unpublished observations …”
Section: Lhmentioning
confidence: 99%
“…The chronic administration of progesterone and 19-norprogesterone produce granulosa cell tumours of the ovaries in BALB mice (Lipschutz et al 1963). …”
Section: Pituitary Tumoursmentioning
confidence: 99%